2017
DOI: 10.1017/s0272263116000449
|View full text |Cite
|
Sign up to set email alerts
|

Pronunciation in Face-to-Face and Audio-Only Synchronous Computer-Mediated Learner Interactions

Abstract: Studies of learner-learner interactions have reported varying degrees of pronunciation-focused discourse, ranging from 1% (Bowles, Toth, & Adams, 2014) to 40% (Bueno-Alastuey, 2013). Including first language (L1) background, modality, and task as variables, this study investigates the role of pronunciation in learner-learner interactions. Thirty English learners in same-L1 or different-L1 dyads were assigned to one of two modes (face-to-face or audio-only synchronous computer-mediated communication) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…Additionally, results revealed that learners perceived the SCMC context as being less stressful and more helpful for language learning. In the same issue, Loewen & Isbell (2017) investigated pronunciation-focused LREs in learner–learner FTF interaction and oral SCMC, finding that only 14% of LREs addressed pronunciation with 90% targeting segmental rather than suprasegmental features. Prior to these studies, much pronunciation-focused interaction research has been conducted by Saito, who in a series of studies (Saito & Lyster 2012; Saito 2013; Saito & Wu 2014; Saito 2015), found mixed results for the effects of interaction and corrective feedback on pronunciation.…”
Section: Linguistic Targetsmentioning
confidence: 99%
“…Additionally, results revealed that learners perceived the SCMC context as being less stressful and more helpful for language learning. In the same issue, Loewen & Isbell (2017) investigated pronunciation-focused LREs in learner–learner FTF interaction and oral SCMC, finding that only 14% of LREs addressed pronunciation with 90% targeting segmental rather than suprasegmental features. Prior to these studies, much pronunciation-focused interaction research has been conducted by Saito, who in a series of studies (Saito & Lyster 2012; Saito 2013; Saito & Wu 2014; Saito 2015), found mixed results for the effects of interaction and corrective feedback on pronunciation.…”
Section: Linguistic Targetsmentioning
confidence: 99%
“…Additionally, recent research findings indicate that task-based instruction (TBI) can be beneficial for L2 pronunciation learning (Gurzynski-Weiss et al, 2017), particularly when learners are exposed to sequences of tasks that increase in complexity (Robinson, 2001, 2005, 2007). This is because TBI prompts more interaction and negotiation of meaning among learners (Loewen and Isbell, 2017; Solon et al, 2017), which improves the perception and production of pronunciation features (Mora and Levkina, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In L2 pronunciation, TBI is effective in segmental (Mora-Plaza et al, 2018; Solon et al, 2017) and suprasegmental learning (Jung et al, 2017; McKinnon, 2017). Additionally, as task complexity increases, learners engage in more negotiation of meaning, producing more pronunciation-focussed language-related episodes (Loewen and Isbell, 2017; Mora and Levkina, 2018; Mora-Plaza et al, 2018; Solon et al, 2017). This is important because of the increase in awareness of linguistic forms, a necessary condition for pronunciation development, and because of the potential improvement in perception and production of such forms (Kennedy and Trofimovich, 2010; Mora and Levkina, 2017, 2018; Venkatagiri and Levis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, explicit corrective feedback has been shown to be more effective for beginners (Li, 2009(Li, , 2014, at least for morphosyntactic features such as Chinese classifiers, and is more easily noticed by learners (e.g., Nassaji, 2009). Furthermore, there is growing interest in computer-mediated communication (CMC) environments and the role they play in facilitating interaction (see Ziegler, 2016 for a meta-analysis), corrective feedback (Parlak & Ziegler, 2017), and L2 pronunciation training (Loewen & Isbell, 2017); however, many of these studies occur in experimental or controlled settings rather than in preexisting online courses. The current study aims to untangle these disparate findings by investigating the effects of more explicit versus more implicit corrective feedback on beginner learners' perception and production of Mandarin tones in a classroom SCMC context.…”
Section: Introductionmentioning
confidence: 99%